Ethical issues in legal practice. Issue 1 (7th December 2018) - Olarra Zorrozúa, Juan Carlos
Abstract: This article analyses the different regulations that affect legal practice in Europe nowadays and the implications derived from those regulations which have evolved significantly in the past decade, to the extent of changing relevant concepts and institutions of the legal profession, from professional secrecy (legal professional privilege or client attorney privilege) to independence of lawyers. It also focuses on the application and interpretation of those regulations by the competent operators, watchdogs, surveillance bodies, courts and judges and even parliamentary chambers, closing with a general reflection on the perception of the role of legal advisors in contemporary societies.